97 Potentially Inappropriate Medications in Patients with Alzheimer's Disease: Data from NILVAD. (16th September 2019) - Murphy, Claire; Dyer, Adam H; Lawlor, Brian; Kennelly, Sean P
Abstract: Background: Prescription of Potentially Inappropriate Medications (PIMs) is common in older adults and is associated with adverse drug events, hospitalisation and mortality. Less well described are the patterns and predictors of PIM usage in patients with Alzheimer's Disease (AD), a patient group who may be particularly vulnerable to polypharmacy and medication associated adverse events. Methods: Secondary analysis of the NILVAD trial, an international phase three trial of Nilvadipine in mild/moderate AD. The v2 STOPP/START criteria were individually applied by a physician to each participant's medication list and cross-reference with their medical history to identify PIM usage. Predictors of PIM usage were modelled using binary logistic regression. Results: Five-hundred and ten patients with AD were included (mean age 72.8 +/-8.3 years; 62% female). The median number of prescribed medications was 5 (IQR 3-7). Over half (55.5%) were prescribed at least one PIM, whilst a minority of patients (14.8%) were prescribed three or more PIMs. The most frequent PIMs were benzodiazepines >4 weeks without indication (n = 55), long-term Proton-Pump Inhibitor (PPI) use without appropriate indication (n = 49), use of non-steroidal analgesics without use of PPI (n=19) and antimuscarinic use in dementia (n= 18). On multivariate analysis, significant predictors of PIM use were higher total number of medications (p=0.001; OR 1.52; 1.36-1.59) in addition to greater AD severity, as rated using the Clinical Dementia Rating Scale Sum-of-Boxes (CDR-sb) (p=0.024; OR 1.18; 1.02-1.35). Conclusion: The majority of older patients with AD were prescribed at least one PIM. Usage of PIMs was associated with greater number of medications and increased dementia severity. Particularly concerning is the potentially inappropriate use of benzodiazepines and anti-muscarinic agents in this population, given recent evidence for the adverse cognitive profile associated with these medications. De-prescribing and medication review interventions aimed particularly at patients with AD are warranted.